Sense of Purpose Following a Dementia Diagnostic Appointment: Comparing Self- and Other-Reports of Care Recipients and Care Partners - Wynn, Matthew J.; Ju, Catherine H.; Hill, Patrick L. (Frontiers in Psychology, 2021)
Objective: Purpose in life tends to decline in older adulthood and it is thought that intact cognitive functioning is required for purposeful living. Thus, it is likely that individuals may perceive older adults who are experiencing cognitive declines associated with dementia as having a reduced sense of purpose. Biases such as these may influence how individuals, especially care partners, interact with those with dementia. Method: This study examined how sense of purpose changed following a dementia diagnostic appointment for both the person receiving a diagnosis and their care partner. This study also explored how each individual perceived the other member of the dyad’s sense of purpose. Older adults (47 care recipients and 75 care partners, 57% female; Mage = 68.5 years, SDage = 12.0 years) provided self- and other-report ratings of sense of purpose before and after their appointment at a specialized memory clinic. Results: Overall, both care recipients and care partners’ sense of purpose declined following a dementia diagnostic appointment (t(85) = 7.01, p < .001). However, when comparing self-reports and other-reports of purpose, care partners reported that care recipients experienced a lower sense of purpose in life than the care recipients reported about themselves. Conclusions: Care recipients and partners reported less purpose in life following their dementia diagnostic appointment. Care partners may hold certain biases regarding sense of purpose towards care recipients. These findings can inform future work regarding how care recipients and care partners can plan purposeful lives following a dementia diagnosis.